Report of the Working Group on Science & Technology for the Sixth Plan (1980-85) - Planning Commission (Planning Commission, 1980)
The Working Group on Science and Technology report for the Sixth Five Year Plan (1980-85) provides a comprehensive roadmap for strengthening India’s S&T sector as a catalyst for economic growth and societal transformation. The report highlights achievements in establishing research infrastructure, universities, and technical institutions, while identifying challenges in underutilization, outdated equipment, and training quality. Key recommendations include enhancing collaboration between research institutions and industry, prioritizing research in agriculture, health, renewable energy, and environmental sustainability, and integrating science education with practical research. The report emphasizes strategic financial planning, performance-based funding, and strengthened inter-ministerial coordination to ensure effective allocation of resources. With focused policy implementation, India is positioned to leverage S&T for national development and improved socio-economic outcomes.
Planning Commission New Delhi (December 1980)
Planning Commission New Delhi (December 1980)
Keywords: Science and Technology; Sixth Five Year Plan; Research Infrastructure; Human Resource Development; Technology Transfer; Innovation; Renewable Energy; Agriculture; Health Technologies; Financial Planning; Institutional Coordination; Socio-Economic Development